Front Cover: Nutritional Lipids and Mucosal Inflammation. Issue 5 (3rd March 2021) - Wawrzyniak, Paulina; Noureddine, Nazek; Wawrzyniak, Marcin; Lucchinetti, Eliana; Krämer, Stefanie D.; Rogler, Gerhard; Zaugg, Michael; Hersberger, Martin
Abstract : Mol. Nutr. Food Res . 2021, 65, 1901269 DOI: 10.1002/mnfr.201901269 In mucosal inflammation, n‐3 polyunsaturated fatty acids enhance the gut barrier function and restore gut microbiota. This is associated with reduced mucosa infiltration of pro‐inflammatory cells and with a shift from pro‐inflammatory to anti‐inflammatory and pro‐resolution mediators. This is reported by Paulina Wawrzyniak, Nazek Noureddine, Marcin Wawrzyniak, Eliana Lucchinetti, Stefanie D. Krämer, Gerhard Rogler, Michael Zaugg, and Martin Hersberger in article 1901269 .